2016
DOI: 10.1097/ijg.0000000000000409
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Same-day Laser Peripheral Iridotomy in the Philadelphia Glaucoma Detection and Treatment Project

Abstract: Performing bilateral, same-day LPI was well tolerated in a large community-based, glaucoma detection and treatment project. Applying this treatment strategy may be considered in similar settings, where patients' access to eye care is limited and it may be a cost-effective strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
(39 reference statements)
1
8
0
Order By: Relevance
“…Same-day bilateral treatments were encouraged. 19 Patients with OAG who declined laser therapy and patients with PACG or secondary angle-closure glaucoma received a prescription for appropriate IOP-lowering medications as determined by the treating ophthalmologist.…”
Section: Methodsmentioning
confidence: 99%
“…Same-day bilateral treatments were encouraged. 19 Patients with OAG who declined laser therapy and patients with PACG or secondary angle-closure glaucoma received a prescription for appropriate IOP-lowering medications as determined by the treating ophthalmologist.…”
Section: Methodsmentioning
confidence: 99%
“…This is consistent with the results of a recent retrospective study, which showed higher rates of immediate IOP elevation in African-Americans following LPI for angle closure. 21 A greater degree of pigment dispersion in thicker, darkly pigmented irides has been suggested to impact IOP elevation and iritis following LPI. [26][27][28][29][30] Consistent with this, patients who racially selfidentified as "Other" also experienced higher rates of post-LPI IOP elevation compared with Whites, which could similarly be because of differences in postlaser pigment dispersion resulting from differences in iris characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…13,15,16 Despite the widespread use of LPI as a routine procedure for many eye care providers, the determinants of shortterm complications following prophylactic LPI for PACS are not well known. Existing studies that investigated post-LPI complications either did not directly compared Nd: YAG and sequential argon-Nd:YAG lasers, 13,[17][18][19][20][21] included mixed cohorts of PACG and primary angle closure (PAC) patients, 13,17,19,21 or were limited to only Asian populations. 13,[18][19][20]22 In addition, while 3 studies examining LPI complications did include Black patients, they were limited by small sample sizes and the inclusion of Nd:YAG laser procedures only.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, community-based bilateral laser PI was found to be cost-effective approach. [10] It is minimally invasive in early cases as extensive peripheral anterior synechia are yet not developed. Although this could be an initial treatment modality for managing chronic angle-closure glaucoma, these patients would need long-term follow-up, and if the IOP is not controlled, other surgeries would be needed after few years.…”
Section: Discussionmentioning
confidence: 99%